The role of inducible NO-synthase isoform in stress-protective activity of antioxidant ethylmethylhydroxypyridine succinate - V. P. Balashov; L. D. Smirnov; L. A. Balykova; N. G. Gerasimova; I. A. Markelova; R. P. Kruglyakov; E. V. Talanova (Российский кардиологический журнал)
The authors analyzed NO-synthase expression in white mice exposed to chronic immobilization stress and receiving intraperitoneal 2-ethyl-6-methyl-3-hydroxypyridine succinate (EMHPS). Immune-hystochemical analysis of left ventricular myocardium was performed by standard method, with primary inducible NO-synthase isoform antibody use. Inducible isoform expression in cardiomyocytes exposed to EMHPS was significantly lower than in chronic immobilization stress without EMHPS administration.